The effect of communication skills and compensation on performance through job satisfaction and subjective well-being of mental hospital nurses in South Sulawesi - Mubyl, Mutiarini; Basalamah, Salim; Rahman Mus, Abdul; Alam, Roslina; Dwinanda, Giri (Edelweiss Applied Science and Technology, 2024)
This research aims to analyze the effect of communication skills and compensation on performance through Work Satisfaction and subjective well-being of mental hospital nurses in South Sulawesi. The research was conducted at RSKD Dadi and involved 100 field samples using a saturated sampling technique. Data were analyzed using structural equation models (SEM) with the SmartPLS4 analysis tool. The research results prove that, directly, Communication skills and compensation have a positive and significant effect on Work Satisfaction; Communication skills and compensation have a positive and significant effect on subjective well-being; Work Satisfaction, communication skills, and subjective well-being have a positive and significant effect on performance; while compensation has no effect on performance. Indirectly, communication skills and compensation have a positive and significant effect on performance through Work Satisfaction; Communication skills and compensation have a positive and significant effect on performance through subjective well-being. In this latest research, it was found that nurses who can improve their communication skills will increase their Work Satisfaction and subjective well-being, so that their performance will also increase.